Internet Accessibility and Use of Online Health Information Resources by Doctors in Training Healthcare Institutions in Nigeria (2015)
The Internet is a global network of networks that enables computers of all kinds to directly and transparently communicate throughout the world. It is described as a global network and an 'Information Super-highway' (Computer Hope 2010). It is defined as a world-wide broadcasting capability, a mechanism for information dissemination, and a medium for collaboration and interaction between individuals and their computers without regard to geographical location (The Internet Society 2010). The internet is indeed a major technological breakthrough of our time. The Internet is a popular source of health information for health care providers and consumers. It has been recognized by many as an important mechanism for transforming medical care. The internet affords healthcare practitioners unprecedented access to huge volume, high quality, current and relevant health care information. Among currently available technologies only the Internet has the potential to deliver universal access to up-to-date health care information (Godlee, Pakenham-Wash et al. 2004). Accurate and up-to-date information is vital to maintain quality of health care. During the past decade, many health information resources have been developed and available online for use by health care professionals. The Internet has been used by healthcare professionals to obtain and share large amounts of medical information and to monitor diseases. The knowledge of the Internet as an important health information resource for physicians have greatly improved during the past decade as a result of patterns of use and medical impact measures (Bennett, Casebeer et al. 2004 ). The Internet has enabled health care practitioners to obtain and share health information and to track and monitor diseases (Centre for Disease Control 2003). In addition, it has made it easy and possible for physicians throughout the world to collaborate, communicate, and interact with each other (Manhas 2008). The Internet has brought about flexible communication between patients and doctors by empowering patients with information. It has also revolutionized the compilation, assessment and distribution of information relating to healthcare (Slattery 2008). In the last two decades, there has been a tremendous increase in the volume of healthcare information published online. The amount of online health information available to users keep growing on daily basis than can ever be imagined ten years back. A great variety of information resources are now available and accessible online. These include among others search engines (Google, Yahoo, Alta Vista, Lycos, Mama, etc) databases (MEDLINE/PubMed, Scopus, Web of Knowledge, EMBASE, African Index Medicus), portals, gateways, digital archives, libraries and institutional repositories. Recent, reliable, quality and up-to-date healthcare information are also available in websites of academic and health institutions, professional associations, governmental and non-governmental organizations. In addition, some governmental and not-for-profit organizations such as the National Institutes of Health (NIH) and Bioline International have digital archives for free full-text articles. Also available online are medical dictionaries, encyclopedias, abstracts and indexes, bibliographies, atlases, videos and drug information sources. Many of these information resources that provide accurate and reliable health care information for medical doctors are results of increase in the pace of healthcare research (Mckibbon, Fridsma et al. 2007) Information is worthless if it is not used. Availability of information is one thing, access to and use of the available information is another (Odutola 2003). According to Dervin and Nilan, “information use” is a process whereby the user tries to make sense of discontinuous reality in a series of information use behavior (Dervin and Nilan 2003). Systems that are not utilized do not result in expected efficiency and effectiveness gains (Agarwal and Prasad 1999). Availability of eresources has changed what users actually read and use; they tend to use what is easily accessible (Renwick 2005). The use of information varies among individuals, and professionals depending on their information needs and status. An important consideration in the process of health information gathering is accessibility and use of such information.